2006
DOI: 10.1590/s0365-05962006000500005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo genético do gene p16 pela técnica de PCR-SSCP e expressão de proteína p16 em melanomas de mucosa oral e melanomas cutâneos

Abstract: FUNDAMENTOS: A deleção e mutação do gene CDKN2a que codifica um inibidor específico da ciclina dependente de quinase 4, a proteína p16, têm sido implicadas na tumorigênese do melanoma cutâneo. Entretanto, pouco se conhece sobre essas alterações genéticas em melanomas de mucosa oral. OBJETIVOS: Verificar a presença de alterações no gene p16 e sua expressão protéica em melanomas esporádicos orais e cutâneos. MATERIAL E MÉTODOS: Avaliaram-se 36 espécimes de melanoma primário (sete orais e 29 cutâneos). Analisaram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…Other authors, however, have not found a correlation between melanoma thickness and the loss of p16 expression 13 . In a recent study of several clinicopathologic types of melanoma, no relationship was found between p16 expression, revealed by immunohistochemistry, and lesion thickness 30 . Such contradictory results may be related to the fact that p16 inactivation is not a strictly timed event in melanoma tumorigenesis 31 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Other authors, however, have not found a correlation between melanoma thickness and the loss of p16 expression 13 . In a recent study of several clinicopathologic types of melanoma, no relationship was found between p16 expression, revealed by immunohistochemistry, and lesion thickness 30 . Such contradictory results may be related to the fact that p16 inactivation is not a strictly timed event in melanoma tumorigenesis 31 .…”
Section: Discussionmentioning
confidence: 97%
“…Such contradictory results may be related to the fact that p16 inactivation is not a strictly timed event in melanoma tumorigenesis 31 . Other possible explanations for the conflicting results could be the use of different methods to demonstrate p16 expression, such as p16 monoclonal 13,27,30 and polyclonal 17,28,29 antibodies, immunohistochemistry, 13,27–30 and flow cytometric analysis 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both steps were developed in a four minute interval each. The positive control was performed with human tonsil (for Ki-67) and dermal nevocellular nevus (for p16) 14 . For negative control, we substituted primary antibody by phosphate buffered saline in the reaction.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%